Factors Affecting Tofu Home Industry Production in Mekar Sari Village, Wasile District - Bayu Adi Priyono; Aziz Hasyim; Nurdin I. Muhammad (IAIN Palopo, 2023)
This study aims to find out what are the factors that influence the production of tofu home industry in Mekar Sari Village, Wasile District, East Halmahera Regency, using quantitative research. The research subjects were tofu entrepreneurs in Mekar Sari Village, Wasile District. The sampling method is random sampling. The sample in this study was 5 entrepreneurs. The data collection method in this study is a questionnaire. The technique used in this study to draw conclusions is multiple linear regression with the Eviews program, resulting in the equation: Y = 665620 +142.9692 x1 + 1397603 x2 - -19.32795 x3 + e. Testing the hypothesis using the R test, shows that the value of R Square is 0.999696 meaning that together the independent variables have an influence of 99.9% on the dependent variable, and 1.1% is influenced by other independent variables not included in this study. It can be concluded that the factors influencing the production of tofu home industry in Mekar Sari Village, Wasile District, East Halmahera Regency. Independent variables Working Capital (X1), Raw Materials (X2), Labor (X3).